2004
DOI: 10.1016/j.jvs.2004.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Serum total 8-iso-prostaglandin F2α: A new and independent predictor of peripheral arterial disease

Abstract: Serum total 8-iso-PGF 2alpha was an independent predictor of PAD in the population studied. This finding supports the hypothesis that 8-iso-PGF 2alpha is a risk marker for PAD. Our results indicate increased systemic oxidative stress in patients with PAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 18 publications
2
31
1
Order By: Relevance
“…The authors suggest that low statistical power could have been a contributing factor with 227 cases and 417 matched controls. This finding disagrees with cross-sectional studies that have shown F 2α -isoprostanes to be predictive for peripheral artery [80] and coronary artery disease [81].…”
Section: Lipid Peroxidation and Cardiovascular Diseasecontrasting
confidence: 98%
“…The authors suggest that low statistical power could have been a contributing factor with 227 cases and 417 matched controls. This finding disagrees with cross-sectional studies that have shown F 2α -isoprostanes to be predictive for peripheral artery [80] and coronary artery disease [81].…”
Section: Lipid Peroxidation and Cardiovascular Diseasecontrasting
confidence: 98%
“…[26][27][28] For example, it has been reported that circulating levels of 8-isoprostane were an independent risk factor associated with coronary artery disease in a Chinese population (odds ratio 2.47, P < 0.001), 26) and were associated with peripheral artery disease. 27,28) In this study, we have shown that valsartan therapy decreased urine 8-isoprostane levels up to 12 months in type 2 diabetic subjects with hypertension, despite the fact that the blood pressure levels were unchanged. Although carotid artery mean IMT did not decrease after 12 months of treatment in this study, there is a possibility that valsartan treatment of a longer period might inhibit the progression of atherosclerosis via suppression of oxidative stress in type 2 diabetic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…After adjustment with age, gender, diabetes, hypertension, BMI, creatinine, LDL, triglyceride, high-sensitivity C-reactive protein and homocysteine, an increment of every 10 pg/mL in serum 8-iso-PGF 2a was associated with an increment of 11% in the risk of lower limb ischaemia (OR ¼ 1.11, 95% CI: 1.03-1.20). 36 …”
Section: Peripheral Artery Diseasementioning
confidence: 99%